Sustainable animal production: exploring the benefits of sperm sexing technologies in addressing critical industry challenges - Quelhas, Joana; Pinto-Pinho, Patrícia; Lopes, Graça; Rocha, António; Pinto-Leite, Rosário; Fardilha, Margarida; Colaço, Bruno (Frontiers in Veterinary Science, 2023)
The sex of the animals is of paramount importance in many animal production systems. This is particularly evident in the production of milk or in breeding programs focused on the production of female animals. In some cases, slaughter or euthanasia of animals of the unwanted sex becomes the only solution, highlighting ethical and economic concerns. As global demand for food continues to rise, the importance of addressing these issues becomes more evident. Reproductive technologies, such as sperm sexing techniques, may hold the key to addressing both animal welfare and the sustainability of animal production. The use of semen enriched with sperm capable of producing offspring of the desired sex can serve as a valuable tool for producers to exert greater control over production outcomes, not only helping to mitigate welfare issues related to the unnecessary premature death of unwanted offspring but also providing a possible ally in the face of stricter animal welfare guidelines. In addition, sexed semen can also contribute to financial gains and reduce greenhouse gas emissions and food waste associated with the less profitable part of the herd. This paper explores the positive impacts that sperm sexing can have on animal welfare, economy, and environment. It also discusses currently available options and strategies for more successful implementation of sexed semen. Partnerships between companies and scientists will be essential to find innovative ways to adapt current production systems and develop sperm sexing technologies that apply to most livestock industries.